Church, state, and the crisis in American secularism - Ledewitz, Bruce, 1975- (Indiana University Press, 2011)
"Since 1947, the Supreme Court has promised government neutrality toward religion, but in a nation whose motto is 'In God We Trust' and which pledges allegiance to 'One Nation under God, ' the public square is anything but neutral--a paradox not lost on a rapidly secularizing America and a point of contention among those who identify all expressions of religion by government as threats to a free society. Yeshiva student turned secularist, Bruce Ledewitz seeks common ground for believers and nonbelievers regarding the law of church and state. He argues that allowing government to promote higher law values through the use of religious imagery would resolve the current impasse in the interpretation of the Establishment Clause. It would offer secularism an escape from its current tendency toward relativism in its dismissal of all that religion represents and encourage a deepening of the expression of meaning in the public square without compromising secular conceptions of government"--Provided by publisher.